2016
DOI: 10.1515/jpm-2015-0206
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with choice of delivery with or without epidural analgesia among laboring women: a cross-sectional survey at a tertiary care hospital of a developing country

Abstract: Patients in developing countries are laboring without EA, even in centers where there is a provision for it. The main reasons for not availing themselves of EA are lack of awareness and knowledge and misconceptions, rather than the desire to have un-medicated natural birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A study conducted in this institution found out that the main reasons for not availing labor epidural service are lack of awareness, knowledge, and misconceptions, rather than the desire to have an unmedicated natural birth. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in this institution found out that the main reasons for not availing labor epidural service are lack of awareness, knowledge, and misconceptions, rather than the desire to have an unmedicated natural birth. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al from Pakistan [9] evaluated the factors responsible for epidural analgesia (EA) refusal among parturient patients. They reported that even though epidural was available, patients in developing countries labored without epidural because of lack of awareness and misconceptions and family pressure about the epidural.…”
mentioning
confidence: 99%